Patient‐specific 3D FLAIR for enhanced visualization of brain white matter lesions in multiple sclerosis. Issue 2 (21st November 2016) - Gabr, Refaat E.; Pednekar, Amol S.; Govindarajan, Koushik A.; Sun, Xiaojun; Riascos, Roy F.; Ramírez, María G.; Hasan, Khader M.; Lincoln, John A.; Nelson, Flavia; Wolinsky, Jerry S.; Narayana, Ponnada A.
Abstract : Purpose: To improve the conspicuity of white matter lesions (WMLs) in multiple sclerosis (MS) using patient‐specific optimization of single‐slab 3D fluid‐attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI). Materials and Methods: Sixteen MS patients were enrolled in a prospective 3.0T MRI study. FLAIR inversion time and echo time were automatically optimized for each patient during the same scan session based on measurements of the relative proton density and relaxation times of the brain tissues. The optimization criterion was to maximize the contrast between gray matter (GM) and white matter (WM), while suppressing cerebrospinal fluid. This criterion also helps increase the contrast between WMLs and WM. The performance of the patient‐specific 3D FLAIR protocol relative to the fixed‐parameter protocol was assessed both qualitatively and quantitatively. Results: Patient‐specific optimization achieved a statistically significant 41% increase in the GM‐WM contrast ratio ( P < 0.05) and 32% increase in the WML‐WM contrast ratio ( P < 0.01) compared with fixed‐parameter FLAIR. The increase in WML‐WM contrast ratio correlated strongly with echo time ( P < 10 ‐11 ). Two experienced neuroradiologists indicated substantially higher lesion conspicuity on the patient‐specific FLAIR images over conventional FLAIR in 3–4 cases (intrarater correlation coefficient ICC = 0.72). In no case was the image quality of patient‐specific FLAIR considered inferior to conventional FLAIR by any of the raters (ICC = 0.32). Conclusion: Changes in proton density and relaxation times render fixed‐parameter FLAIR suboptimal in terms of lesion contrast. Patient‐specific optimization of 3D FLAIR increases lesion conspicuity without scan time penalty, and has potential to enhance the detection of subtle and small lesions in MS. Level of Evidence: 1 Technical Efficacy : Stage 1 J. MAGN. RESON. IMAGING 2017;46:557–564